PENGARUH PENGGUNAAN PEMBELAJARAN ARTICULARE STORYLINE TERHADAP HASIL BELAJAR MATEMATIKA KELAS V - Pasinggi, Yonathan. S; Muslimin, Muslimin; Jalil, Abdul Jalil (Universitas Negeri Makassar, 2024)
This study examines the effect of using ArticulateStoryline Learning Media on Mathematics learning outcomes for class V UPTD SD Negeri 25 Parepare. Study. The research approach used is a quantitative approach with a Pre-Experimental type. The population of this study was all students in class V UPTD SD NEGERI 25 Parepare for the 2023/2024 academic year, totaling 27 people. This research focuses on the influence of using Articulate Storyline Media on student learning outcomes. Data collection techniques are tests and documentation. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis consisting of normality tests and hypothesis tests using Paired Sample T-Test. Furthermore, the results of the hypothesis test were carried out using the Paired Sample T-Test which showed that H1 was accepted, meaning that there was a difference in the average mathematics learning outcomes for flat shape material in class V UPTD SD Negeri 25 Parepare between before and after the Articulate Storyline learning media was applied. Thus, the conclusion of this research shows that there is an influence of the application of Articulate Storyline Learning Media on the Mathematics Learning Outcomes of class V students..Keywords: Articulate Storyline; Mathematics; Learning Outcomes learning media.